Strategi Peningkatan Produktivitas Kinerja Karyawan Pada Franchise Mixue di Lubuk Begalung - Hamdani Hamdani; Nadia Putri Yasma; Deri Farma; Arib Aufa; Vivi Nila Sari (Jurnal Transformasi Bisnis Digital, 2025)
This research aims to find out how the training provided by Mixue to its employees is to increase the productivity of its employees' performance through questions and answers to obtain the necessary information. This research uses a qualitative, descriptive approach in the form of in-depth interviews with Mixue employees in Lubuk Begalung. The strategy to increase employee performance productivity is an effort made by the company to improve employee performance so that it can be used for the good and progress of the company. In order to achieve the desired targets, companies must develop appropriate strategies. It involves management-oriented human resource planning through a specific set of actions. Productivity refers to an employee's ability to complete tasks according to standards in terms of completeness, cost, and speed, which reflects the utilization of human resources in an efficient and effective manner in the company. Efforts that have been made by Mixue to increase employee performance productivity are by providing skills in the form of introducing SOPs, (1) Carrying out training, (2) Appraising employee performance, (3) Career path (career development), and (4) Conduct regular performance evaluations